2019
DOI: 10.1002/ijgo.12941
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti‐Müllerian hormone is associated with oocyte dysmorphisms and ICSI outcomes

Abstract: Objective: To evaluate the association between serum levels of anti-Müllerian hormone (AMH) and oocyte dysmorphisms in intracytoplasmic sperm injection (ICSI) cycles. Methods:A retrospective study of data from 628 ICSI cycles with successful oocyte retrieval carried out at a single center in Tehran from November 2015 to July 2018.Cycles were divided into six groups by serum AMH level. Various oocyte dysmorphisms, quantity of retrieved oocytes, fertilization rates, cleavage-stage embryos, and pregnancy rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…Compared with women with elevated levels of FSH but lower levels of AMH, women with variable serum AMH levels that are greater than or equal to 0.6 ng/ml had more oocytes retrieved, more embryos on day 3, and a lower transfer cancellation rate ( 33 ). Another study concluded that serum levels of AMH were associated with specific oocyte dysmorphisms and an average oocyte quality index ( 34 ). The rates of fertilization and high-quality embryos are crucial aspects affecting blastocyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with women with elevated levels of FSH but lower levels of AMH, women with variable serum AMH levels that are greater than or equal to 0.6 ng/ml had more oocytes retrieved, more embryos on day 3, and a lower transfer cancellation rate ( 33 ). Another study concluded that serum levels of AMH were associated with specific oocyte dysmorphisms and an average oocyte quality index ( 34 ). The rates of fertilization and high-quality embryos are crucial aspects affecting blastocyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years AMH has been shown to represent a reliable marker of ovarian reserve and ovarian stimulation response (Fridén et al, 2011;Brugo Olmedo et al, 2013). Although knowledge of the physiologic role of AMH remains limited, various studies have demonstrated its importance as regulator of ovarian activity (Azizi et al, 2019). AMH, a member of the transforming growth factor-β family, has the primary role of regression of the Müllerian duct in the male fetus during early testis differentiation, persisting after completion of the male reproductive system, and commencing in females in early fetal life, produced by ovarian granulosa cells (Nelson et al, 2007;Brugo Olmedo et al, 2013) of pre-antral and small antral follicles (Nelson et al, 2007;Lee et al, 2009;Fridén et al, 2011;Brugo Olmedo et al, 2013;La Marca et al, 2017).…”
Section: Ovarian Reservementioning
confidence: 99%
“…Additionally, as granulosa cells exert important roles in folliculogenesis, AMH could also influence the quality of oocytes (Azizi et al, 2019).…”
Section: Ovarian Reservementioning
confidence: 99%
See 2 more Smart Citations